PENGEMBANGAN APLIKASI SEJARAH LOKAL BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN MAHASISWA FKIP SEJARAH UNIVERSITAS RIAU - Gita febriana Hutapea; Bedriati Ibrahim; Isjoni Isjoni (Jurnal Pendidikan, 2022)
Riau Province has a variety of history which is certainly important in the field of learning, especially history learning. This study aims to determine the condition of lectures in local history courses in terms of the development of history student learning media, to find out an increase in the development of android-based local history applications as student learning media, to find out how much effective Android-based Pekanbaru local history applications are as student learning media. Data were collected using a questionnaire (questionnaire), interviews, observations, and documentation. The subjects of this study were students of history education at the University of Riau from class 2018, 2019, and 2020. The data analysis technique used qualitative and quantitative analysis techniques. The results of the study showed that overall, learning media using EHP that had been developed by researchers could be tested, and the media aspect obtained an average of 89% which was included in the valid category. Student participant responses stated that the EHP learning media could attract students' attention and interest in learning, the use of language was simpler and easier to understand.